Peran Perkembangan Sektor Keuangan terhadap Industrialisasi di Indonesia - Hari Setia Putra; Shaghi Ratu Sa’bani; Syifa Ananda; Ullya Vidriza (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2021)
The aim of this research is to analyze the impact of financial development in industrialization in Indonesia for the period 1990 to 2019 using time series data. The data used are ratio of broad money to GDP, ratio of domestic credit to private sector to GDP, and interest rate spread. The results of the pairwise granger causality test in the VECM analysis phase prove that there is a one-way relationship beetwen domestic credit to private sector ratio with broad money ratio and broad money ratio with interest spread rate. Meanwhile, the interest spread rate and domestic credit to private sector ratio have a two-way relationship. Impulse response results show that the industry value added ratio responds most to interest spread rate shocks compared to other variables. Variance decomposition results show that the contribution given by interest spread rate to the industry value added ratio is relatively the largest compared to the contribution given by broad money ratio and domestic credit to private sector ratio.